EKSISTENSI DIRI MAHASISWA DALAM KETERLIBATAN PADA MARCHING BAND UNIVERSITAS GADJAH MADA - , WIRAINA AZALIA RAHMAWULAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Humans are social creatures which require interaction between individuals to live in the community. It is In accordance with what was said by Mac Iverdan Charles H.Page (Soekanto, 1975: 96) regarding the need for people to form a small entity or group. The motive of the formation of the group or organization can be derived from a common hobby or avocation of each forming an organization, one example is the organization of Marching Band. Marching Band is one of the GMU student activities at GMU units engaged in the art known to have solid training activities so many consequences to be borne when involved in Marching Band UGM. The purpose of this study was to determine why the student chose marching band activities as an extracurricular activity in UniversitasGadjahMada, benefits and impacts obtained after engaging in activities Marching Band UGM. The method used is a qualitative method with interviews as a data collection technique is supported by the observation and study of literature. Qualitative methods are considered able to provide a comprehensive overview over the problems examined so as to provide an explanation along with a clear and complete translation. The data obtained were analyzed descriptively to achieve a conclusion about the problems studied. From the results of this study concluded that students in choosing a rational choice Marching Band UGM influenced by two factors: internal and external. The internal factor is student's perception of the integrity Marching Band UGM and rational choice influenced by several factors, among others, the existence of social relations that drive. Rational choice arises when one wants to achieve a certain goal where in the Marching Band UGM, students have the motive behind participation. External factors such as appearance representation Marching Band UGM has prestige in the community and leadership that promotes Marching Band UGM personal approach so as to create a sense of family that is high in Marching Band UGM. Other findings are emerging impact of student participation in an organization. The impact arising from participation in the Marching Band UGM there are two negative and positive impacts. Density of training activities have an impact on the lack of student study hours and not the establishment of good social relations with \\"peergroup\\" on campus which led to decline in student academic achievement. Then the positive impact is the development of the ability of member organizations in the field of music and relate to the condition Marching Band UGM gender bias among members of both men and women where there is no division of labor by sex but by kemaun and the ability of members, as well as strong relationships with fellow members and to instill a sense of confidence to each GMU Marching Band members became a tool to improve student self existence.